Of Mice and Canines: Anthropomorphizing Animals in Art Spiegelman’s Maus - Regmi, Laxmi; Panta, Shiva Raj (Shahid Kirti Multidisciplinary Journal, 2025)
This research article is mainly concerned with the wide-ranging interpretation of animal metaphors especially the dogs and mice in the graphic novel Maus. In the novel, the mice are the stand-in for the Jews, and the American are taken as dogs. Pondering the metaphor’s aptness and authenticity, the study employs the theories of metaphors and interrogates the metaphorical use of mice and canines in the novel. The methodology of the study is informed by the close readings of the grammatextuality. The analysis of the verbal and visual texts of the graphic novels is carried out by the comparative analysis method. The relation of the verbal and visual sections of the graphic novel are further elucidated by the analysis of the arrangement of the images. In order for the interpretation and the analysis of the evidence collected, an analytical framework consisting of two concepts: suppression of differences and the contradictions of internal validity has been developed so that the mice and canine metaphors in the verbal and visual texts are examined. The graphic novel that has drawn the attention of cognitive linguists to Posthuman animal studies scholars yields an argument: the metaphors employed in this novel lack aptness and authenticity. The researcher argues that the comparison of Americans as dogs and Jews as mice has been interrogated and charged the simplistic and shallow use of metaphor that has created internal inconsistency and turns out to be the inappropriate comparison.